The development of a vocabulary instruction model for content and language integrated learning for English language learners in Bangkok - Robert Alexander McBain; Nathara Mhunpiew (Universidad de La Sabana, 2014)
This paper presents a research project on content vocabulary instruction with a focus on the development of a model to improve vocabulary learning in a content language integrated learning (CLIL) environment. The model was based on Cronbachs 1942 and Stahl and Fairbanks 1986 theories of vocabulary learning which emphasise a progressive approach starting at a basic level and then an intermediate level and which culminates to a  productive stage of specific vocabulary. The model also relates to the analysis of classroom discourse which highlights the importance of a student centered learning approach where emphasis is placed on encouraging students to progress more at their own pace and in their own time rather than the circumstances set by the teacher, in light of concerns over the amount of and frequent use of content vocabulary; while studying major theories in content area studies.